1999
DOI: 10.1097/00000421-199902000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Accrual to Breast Cancer Clinical Trials at a University-Affiliated Hospital in Metropolitan Detroit

Abstract: Despite the large number of available studies, most women with breast cancer do not participate in clinical trials, and this is especially true among lower income and minority women. In this study the authors surveyed the practice patterns of four medical oncologists who comprised the clinical breast service at a large urban university hospital to develop a better understanding of the clinical trials enrollment process for women with breast cancer. Of 136 new female breast cancer patients seen by the four phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Numerous studies have demonstrated racial disparities in clinical trial accrual [7][8][9] ; our results suggest that these differences may in part reflect access to trials or reservations about specific study procedures, 25 rather than a general aversion to clinical research. Consistent with previous reports, 26,27 older patients in this cohort seemed less willing to be recruited for future research studies.…”
Section: Order Enrolledsupporting
confidence: 90%
“…Numerous studies have demonstrated racial disparities in clinical trial accrual [7][8][9] ; our results suggest that these differences may in part reflect access to trials or reservations about specific study procedures, 25 rather than a general aversion to clinical research. Consistent with previous reports, 26,27 older patients in this cohort seemed less willing to be recruited for future research studies.…”
Section: Order Enrolledsupporting
confidence: 90%
“…EVorts to understand why minorities in the US are frequently underrepresented in the conduct of clinical trials have identiWed a number of important issues likely to contribute to the current state-of-aVairs, including socioeconomic factors, insurance coverage, mistrust of the medical and research establishments, inadequate awareness of relevant studies, and lack of access (Lara et al 2005;Moreno-John et al 2004;McCaskill-Stevens et al 1999;Simon et al 1999;Lai et al 2006). Clearly, no simple "Wx" to solve this vexing problem will be found.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that a common reason for patient ineligibility to available protocols is narrow eligibility criteria. 3,14,21,22,23,24 Trial eligibility attempt to satisfy two opposing criteria. On the one hand, eligibility must be sufficiently narrow to produce a treatment effect that is approximately consistent across the cohort.…”
Section: Understanding Barriers To Clinical Trial Participationmentioning
confidence: 99%